Effects of dry-salting and brine-pickling processes on the physicochemical properties, nonvolatile flavour profiles and bacterial community during the fermentation of Chinese salted radishes. (1st March 2022) - Tang, Yao; Chen, Gong; Wang, Dongdong; Hu, Rong; Li, Heng; Liu, Shuliang; Zhang, Qisheng; Ming, Jianying; Chi, Yuanlong
Abstract: The profiling of physicochemical properties, nonvolatile flavour compounds and bacterial community during the fermentation of Chinese dry-salted and brine-pickled radishes was performed. Dry-salted radishes matured on the 30th day, and the pH, total titratable acid, and water activity of the matured samples were 4.7, 0.43 g/100 g lactic acid, and 0.90, respectively. Brine-pickled radishes matured in only 5 days, and the pH, total titratable acid, and water activity were 3.4, 0.31 g/100 g lactic acid, and 0.96, respectively. The contents of reducing sugars, organic acids, and free amino acids generally increased with the fermentation of dry-salted radishes, reaching 15.8 g/100 g, 1009.1 mg/100 g, and 300.3 mg/100 g on the 30th day, respectively. Lactic acid was the characteristic flavour substance of brine-pickled radishes. Exiguobacterium, Glutamicibacter, and Leuconostoc were the dominant genera when the dry-salted radishes matured. Lactobacillus dominated brine-pickled radish fermentation and was correlated to lactic acid, Arg, Val, and His ( P<0.05 ). This study could improve our understanding of the effects of dry salting and brine pickling on the flavour and bacterial characteristics of salted vegetables. Highlights: Effects of dry salting and brine pickling on flavour and microbial properties were studied. Dry salting helped to the formation and accumulation of nonvolatile flavour compounds. Dry-salted radishes took longer period to maturation and had higher pH and lower TTA. Brine pickling favored the conversion of reducing sugars into organic acids. Lactobacillus was correlated with lactic acid and free amino acids in brined radishes.